Hurricane Preparation: Evacuating Your Home - Elizabeth B. Bolton (EDIS)
During the months of potential hurricanes, it is important to plan for the worst and hope that it never happens. For example, you and your family may be asked to leave your home due to some emergency conditions in your community. Your local emergency officials will not ask you to leave your home or location unless there is a valid reason. Do not try and second-guess the validity of their request. Do as they say immediately. Most of the time these requests and related information will come through radio broadcasts or the local TV station. Different warning methods may be used such as a siren or telephone calls. This document is FCS3254, one of a series of the Family Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June, 2005.